The endothelial-immunothrombotic storm in viral sepsis: lessons from COVID-19 - Zhou, Kaihuan; Chen, Yin; Pang, Jielong; Zhang, Jianfeng; Lu, Junyu (Frontiers in Immunology, 2026)
Taking COVID-19 as an illustrative example, this review systematically elucidates the central pathological mechanism of viral sepsis, termed the endothelial-immunothrombotic storm. This mechanism is initiated by the direct viral infection of endothelial cells, which provokes excessive immune activation and disrupts coagulation through immunothrombosis, including cytokine storms, NETosis, and complement activation. Meanwhile, these processes establish a vicious cycle leading to multiple organ failure. Compared with classical bacterial sepsis, viral sepsis exhibits distinctive features such as interferon dysregulation, direct endothelial damage, a hypercoagulable state, and T-cell exhaustion. This review integrates the latest research findings, contrasts the pathophysiological differences between viral and bacterial sepsis, and proposes precision strategies focused on endothelial protection, immune modulation, and anticoagulation. Finally, we discuss the clinical translational prospects of these approaches and suggests directions for future research.